Amelanotic corneally displaced malignant conjunctival melanoma: a case report evaluated with impression cytology - Barros,Jeison de Nadai (2014)
Here we describe the case of a 65-year-old Caucasian female who presented with an amelanotic malignant conjunctival melanoma and highlight the clinical and pathological features of this rare entity that displayed exclusive corneal invasive growth without evidence of conjunctival tumors other than primary acquired melanosis. Impression cytology aided in the initial diagnosis. The patient underwent surgical treatment. Histopathology and immunohistochemistry revealed an invasive amelanotic melanoma limited to the cornea and exhibiting S-100, Melan A, and HMB-45 positivity. The absence of pigmentation delayed early clinical detection and treatment. Awareness of this nonpigmented melanoma is important for early recognition and appropriate management.